2014
DOI: 10.3389/fpls.2014.00628
|View full text |Cite
|
Sign up to set email alerts
|

Progress of cereal transformation technology mediated by Agrobacterium tumefaciens

Abstract: Monocotyledonous plants were believed to be not transformable by the soil bacterium Agrobacterium tumefaciens until two decades ago, although convenient protocols for infection of leaf disks and subsequent regeneration of transgenic plants had been well established in a number of dicotyledonous species by then. This belief was reinforced by the fact that monocotyledons are mostly outside the host range of crown gall disease caused by the bacterium and by the failures in trials in monocotyledons to mimic the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 90 publications
2
81
0
8
Order By: Relevance
“…Likewise, the number of transformation sites (blue spots per embryo) was also lower for the BR 451 (11.7) compared to Hi-II (14.6) (Figure 1). Differences among maize genotypes in the capacity to be infected have been widely reported in the literature (Huang & Wei, 2005;Frame et al, 2006;Omer et al, 2013;Ombori et al, 2014;Souza et al, 2017), with genotype dependence being the main limitation in maize genetic transformation by this method (Hiei, Ishida, & Komari, 2014). Genotypic differences can be explained by compatibility variation between maize genotype and the bacterial strain employed in the transformation or the T-DNA transference machinery encoded by the bacteria and plant cell genomes (Ombori et al, 2014;Lowe et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the number of transformation sites (blue spots per embryo) was also lower for the BR 451 (11.7) compared to Hi-II (14.6) (Figure 1). Differences among maize genotypes in the capacity to be infected have been widely reported in the literature (Huang & Wei, 2005;Frame et al, 2006;Omer et al, 2013;Ombori et al, 2014;Souza et al, 2017), with genotype dependence being the main limitation in maize genetic transformation by this method (Hiei, Ishida, & Komari, 2014). Genotypic differences can be explained by compatibility variation between maize genotype and the bacterial strain employed in the transformation or the T-DNA transference machinery encoded by the bacteria and plant cell genomes (Ombori et al, 2014;Lowe et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…According to Hiei et al (2014), high temperature during co-cultivation may also result in agrobacteria overgrowth in the co-cultivation medium. The present study showed that high temperature (28°C) was unfavorable for transient transformation but did not promoted bacterial overgrowth even during a prolonged co-culture period.…”
Section: Resultsmentioning
confidence: 99%
“…This result confirms the fact that the resistance of selected calli to chlorsulfuron is due to the expression of the ALS transgene. Despite the progress and the new interest in using Agrobacteriummediated methods for in vitro transformation of graminaceous (Jha et al, 2011;Sharma et al, 2011;Plaza-Wüthrich and Tadele, 2012;Hiei et al, 2014), the particles bombardment is still an effective technique for the introduction of transgenes in monocot plant cells with an average transformation frequency of more than 50% (Goldman et al, 2003). Thus, our results indicate that the biolistic method is suitable for in vitro transformation of P. glaucum varieties of Côte d'Ivoire because these varieties are recalcitrant to plants regeneration from protoplasts (Tiécoura et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As compared to dicotyledons plants, graminaceous are recalcitrant to transformation methods using the Ti plasmid as vector (Plaza-Wüthrich and Tadele, 2012;Hussain et al, 2013;Sah et al, 2014). The major obstacles to this gene delivery method were attributed to the limited host-range of Agrobacterium (Hwang et al, 2013;Qamar et al, 2015), and to the different responses of monocots (cell death) and dicots (cell division) to wounds (Potrykus, 1990;Hiei et al, 2014). A variety of techniques such as polyethylene glycol (PEG) method, electroporation method, mild ultrasonication and biolistic have been proposed for genetic transformation of cereals.…”
Section: Introductionmentioning
confidence: 99%
“…Recalcitrance to tissue culture and transformation limits efforts to use transgenesis and genome editing for crop functional genomics research (Shrawat and Lörz, 2006;Hiei et al, 2014). Efficient Agrobacterium-mediated transformation is typically limited to a narrow range of genotypes within a species (Nam et al, 1997).…”
Section: Increasing Transformation Efficiency In Crops: Improving Eximentioning
confidence: 99%